Analysis of Financial Performance Before and After the Implementation of PSAK 116 on Lease (Empirical Study on Infrastructure Companies in the Telecommunication Sub-Sector Listed on the IDX) - Muhammad Rizky Firmansyah Muhammad; Hurriyaturrohman Hurriyaturrohman; NA Rumiasih (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2025)
The implementation of PSAK 116 brings significant changes to a company's financial statements because it requires the lessee to recognize the right to use the leased asset and the obligation to pay rent if the lease term is more than 12 months. This study aims to examine the differences in the company's financial performance before and after the implementation of PSAK 116, with the object being a telecommunications infrastructure company listed on the Indonesia Stock Exchange (IDX) and having implemented this standard since 2020. The research method uses a quantitative approach with secondary data from the 2020–2021 annual reports. The variables studied include solvency ratios (Debt to Equity Ratio, Debt to Asset Ratio) and profitability ratios (Return on Assets, Return on Equity). The analysis was conducted using a Paired Sample t-Test. The results show that PSAK 116 has a significant effect on financial ratios, especially on the solvency ratio, while the impact on profitability varies between companies according to their respective characteristics. The implementation of PSAK 116 is considered to increase the transparency of financial reports and provide a more realistic picture of the company's financial position and ability to generate revenue. Keywords: PSAK 116, financial performance, solvency